Screening the elite chemotypes of Gloriosa superba L. in India for the production of anticancer colchicine: simultaneous microwave-assisted extraction and HPTLC studies - Pandey D.K.; Kaur P.; Kumar V.; Banik R.M.; Malik T.; Dey A. (My University, 2025)
Background: Gloriosa superba L. (Colchicaceae) is a high-value medicinal plant indigenous to Africa and Southeast Asia. Its therapeutic benefits are well-established in traditional medicines including Ayurveda. It is well known for its natural bioactive compound colchicine which exhibits a wide range of pharmacological activities i.e. rheumatism, gout and was also introduced into clinical practices. The increasing demand as well as its illegal harvesting has brought this valuable plant under threatened category. Methods: The present investigation describes a microwave assisted extraction (MAE) strategy coupled with a densitometric-high performance thin layer chromatographic (HPTLC) methodology for the analysis of colchicine from 32 different populations of G. superba. A Box-Behnken statistical design (3 level factor) has been employed to optimize MAE, in which power of microwave, time of irradiation, aqueous ethanol and pH were used as independent variables whereas colchicine was used as the dependent variables. Chromatography was carried out on Silica gel 60 F254 TLC plates with toluene: methanol, 85:15 (v/v) being used as solvent system. Densitometric measurement was performed at λ=254 nm following post-derivatization (10% methanolic sulphuric acid). Results: Optimal conditions for extraction to obtain the maximum colchicine yield was found to be 7.51 mg g− 1 which was very close to be predicted response 7.48 mg g− 1 by maintaining microwave power (460 W), irradiation time (6.4 min), aqueous ethanol-30, pH -3. Colchicine content ranged between 2.12–7.58 mg g− 1 among 32 G. superba populations in which only three chemotypes viz. GS- 1, GS- 3, and GS- 2 collected from West Bengal and Sikkim, respectively exhibited maximum yield of colchicine. Conclusion: Therefore, this newly developed optimized MAE coupled with HPTLC densitometry methodology not only quantifies colchicine in order to identify elite chemotypes of G. superba, but it also encourages in selecting high yielding populations of the plants for industrial use and economic boost for the farmers. This validated, simple and reproducible HPTLC protocol is being used for the first time to estimate colchicine from natural populations of G. superba obtained from 32 different geographical regions of India. Graphical abstract: [Figure not available: see fulltext.] © 2021, The Author(s).